Henry Barton Jacobs, William Osler's Intimate Friend. Issue 1 (1st January 2017) - Bryan, Charles S.
Abstract : William Osler was considered a universal friend by physicians of his era but, as with most people, his intimate friends were few. Henry Barton Jacobs became a close friend as one of the "latchkeyers" who lived next door to the Oslers in Baltimore, and the friendship intensified after Jacobs married Mary Sloan Frick Garrett, the fabulously wealthy widow of a former patient. The couples stayed close after the Oslers moved to Oxford, vacationing together and corresponding frequently. The couple friendship between the Oslers and the Jacobses benefited American medicine in specific ways, including the care of patients with tuberculosis and the care of children.